Poly-isoprenylated ifosfamide analogs: Preactivated antitumor agents as free formulation or nanoassemblies - Skarbek, Charles; Delahousse, Julia; Pioche-Durieu, Catherine; Baconnais, Sonia; Deroussent, Alain; Renevret, Patrice; Rivard, Michael; Desmaele, Didier; Martens, Thierry; Le Cam, Eric; Couvreur, Patrick; Paci, Angelo (International journal of pharmaceutics, 2017)
[Display omitted] Oxazaphosphorines including cyclophosphamide, trofosfamide and ifosfamide (IFO) belong to the alkylating agent class and are indicated in the treatment of numerous cancers. However, IFO is subject to limiting side-effects in high-dose protocols. To circumvent IFO drawbacks in clinical practices, preactivated IFO analogs were designed to by-pass the toxic metabolic pathway. Among these IFO analogs, some of them showed the ability to self-assemble due to the use of a poly-isoprenyloxy chain as preactivating moiety. We present here, the in vitro activity of the nanoassembly formulations of preactivated IFO derivatives with a C-4 geranyloxy, farnesyloxy and squalenoxy substituent on a large panel of tumor cell lines. The chemical and colloidal stabilities of the geranyloxy-IFO (G-IFO), farnesyloxy-IFO (F-IFO) and squalenoxy-IFO (SQ-IFO) NAs were further evaluated in comparison to their free formulation. Finally, pharmacokinetic parameters and maximal tolerated dose of the most potent preactivated IFO analog (G-IFO) were determined and compared to IFO, paving the way to in vivo studies.